Effects of a Motor Intervention Program on Motor Skills and Executive Functions in Children With Learning Disabilities. Issue 3 (June 2019) - Emami Kashfi, Toktam; Sohrabi, Mehdi; Saberi Kakhki, Alireza; Mashhadi, Ali; Jabbari Nooghabi, Mehdi
This study examined the effect of a motor intervention based on the attention, balance, and coordination (ABC) learning approach on motor proficiency and executive functions in children with learning disabilities (LD). Forty-five male elementary school students with LD aged 7-9 years were recruited and randomly assigned into one of three groups: two experimental groups and one control group. Experimental Group A received only the motor intervention. Experimental Group B simultaneously received both motor intervention and regular educational services. The control group received only regular educational services. The motor intervention involved sequential station exercises based on ABC; this training took place in 24 sessions, scheduled three times a week for eight weeks. We obtained children's scores on the Bruininks-Oseretsky Tests of Motor Proficiency, N -Back Test, Tower of London, and Continuous Performance Tests at pretest, posttest, and follow-up testing. Our results showed that both experimental groups significantly improved their motor skills and most measures of executive functions, relative to no significant improvement for the control group. The improvements on some measures of executive functions in Experimental Group B were just slightly better than in Experimental Group A. This study supported Blythe's ABC learning approach emphasizing ABC, and it extended earlier findings of benefits of this approach to populations of children with LD.